Economic-Pragmatic Interaction in Traditional Market Transactions: An Analysis of Seller–Buyer Conversations at Pasar Kodim Pekanbaru - Lusi Komala Sari; Muhammad Akbar; Lucy Mgbemgasha Apakama (Actual Insight, 2025)
This study investigates economic-pragmatic interactions in traditional market transactions, focusing on seller–buyer conversations at Pasar Kodim. Using a qualitative approach, data were collected through direct observation, audio recordings, and brief interviews with sellers to capture natural dialogues, negotiation patterns, and social dynamics. The analysis revealed that sellers employ pragmatic strategies, including persuasive speech acts and flexible pricing, while buyers use questions and clarifications to ensure fairness and optimal outcomes. Politeness strategies, such as warm forms of address and inquiries about personal background, foster social rapport and facilitate negotiation, reflecting positive politeness in action. The study also highlights the integration of cultural and economic values, as sellers emphasize the benefits of locally produced goods over imported products, thereby linking transactional language to national identity and socio-cultural norms. Findings demonstrate that traditional market communication involves a synergistic combination of linguistic, economic, and social considerations, where effective transactions rely on both strategic language use and interpersonal harmony. The study contributes to the understanding of economic-pragmatic behavior in natural contexts, offering insights for sociolinguistics, pragmatic analysis, and market communication strategies. Implications include the potential application of language-based approaches to enhance negotiation effectiveness and promote local products in culturally resonant ways.